A CASE REPORT ON EXTRANODAL NATURAL KILLER/T-CELL LYMPHOMA (ENKTCL) IN A CAUCASIAN ADULT - Trpkovska Terzieva, Slobodanka; Gjeorgjieva Janev, Olivera; Terzieva, Andonija; Mojsovska, Tara; Sotirova, Tatjana; Pavkovikj, Marica; Genadieva Stavrikj, Sonja; Stojanoski, Zlate (Journal of Morphological Sciences, 2025)
Peripheral T-cell lymphomas (PTCLs) are uncommon entities, accounting for fewer than 10% of all non-Hodgkin lymphomas. Initial evaluation of PTCLs includes history and physical examination, computed tomography (CT) of the chest, abdomen and pelvis or positron emission tomography (PET)/CT imaging, a marrow aspirate and a biopsy. Extra nodal NK/T-cell lymphoma (ENKTL) represents approximately 5% of PTCLs. Although the disease typically appears as a localized tumour at the initial diagnosis with a low (favorable) International Prognostic Index (IPI) and without B-symptoms, recurrence and frequent relapses are the main threats to the course of ENKTL. For this reason, patients with stage 1 of the disease have a worse outcome compared to those who initially appear with a tumor mass at other locations. We hereby present a case of a 38-year-old male patient, who firstly appeared with a localized mass in one of the testicles. Despite properly treating the condition with first-, second- and third-line chemotherapeutics plus adjuvant radiotherapy, the patient has had a total of two relapses in the past 4.5 years. After the last given regimen, the patient has been disease-free for three months, which is not an encouraging time given the cumulative side effect of polychemotherapy and the aggressiveness of the disease itself. Keywords: natural killer/T-cell lymphoma, testis, 18 F-FDG PET.